1994
DOI: 10.1039/dt9940000007
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenation catalysis by an iron porphyrin and its application to α,β-unsaturated esters

Abstract: Chloro(5,I 0.1 5,2O-tetraphenylporphyrinato)iron(rrr) in tetrahydrofuran-methanol catalysed the hydrogenation of a,P-unsaturated esters by NaBH, to the saturated esters; turnovers of up to 4580 h-' have been attained for the hydrogenation of ethyl 2-methylbut-2-enoate. Deuterium labelling studies showed that * Proton NMR spectroscopy shows that the signal of NaBH, does not decrease at all in the thf-CD30D solution clearly indicating that NaBH, undergoes no H-D exchange.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Both of these powerful methods proved excellent for the reduction of mono‐ and disubstituted alkenes, but were not active in the hydrogenation of trisubstituted alkenes and used catalysts which are highly air‐ and‐moisture sensitive 9f. Iron‐porphyrin complexes in conjunction with NaBH 4 have been used to catalyse the reduction of electron‐deficient alkenes,11 including α,β‐unsaturated esters,11b,12 and Ashby and co‐workers showed that stoichiometric amounts of iron(II) chloride and LiAlH 4 would reduce mono‐ and disubstituted alkenes in good yield 13. Most recently Boger and co‐workers have used superstoichiometric amounts of an iron salt and borohydride reagent for the reductive functionalisation of alkenes with electrophiles 14…”
Section: Methodsmentioning
confidence: 99%
“…Both of these powerful methods proved excellent for the reduction of mono‐ and disubstituted alkenes, but were not active in the hydrogenation of trisubstituted alkenes and used catalysts which are highly air‐ and‐moisture sensitive 9f. Iron‐porphyrin complexes in conjunction with NaBH 4 have been used to catalyse the reduction of electron‐deficient alkenes,11 including α,β‐unsaturated esters,11b,12 and Ashby and co‐workers showed that stoichiometric amounts of iron(II) chloride and LiAlH 4 would reduce mono‐ and disubstituted alkenes in good yield 13. Most recently Boger and co‐workers have used superstoichiometric amounts of an iron salt and borohydride reagent for the reductive functionalisation of alkenes with electrophiles 14…”
Section: Methodsmentioning
confidence: 99%
“…The fused 5,5‐ring system allows for diastereoselective transformations. Conjugate reduction using NaBH 4 /Fe(tpp)Cl generates the exclusive saturated ester diastereomer ( 18 ) [37] . The enoate is also poised for subsequent cycloadditions.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugate reduction using NaBH 4 /Fe(tpp)Cl generates the exclusive saturated ester diastereomer (18). [37] The enoate is also poised for subsequent cycloadditions. Nitrile oxide addition [38] affords isoxazoline 19 with excellent regioselectivity and moderate dr, while Ag-catalyzed glycine-imine (3 +2) cycloaddition [39] yields pyrrolidine 20 featuring six stereogenic centers.…”
Section: Table 1: Evaluation Of Photocatalyzed Indole (3+2) Cycloaddi...mentioning
confidence: 99%